Distribution and population structure of the flecked box crab Hepatus pudibundus (Decapoda, Brachyura) in the western South Atlantic - de Lima, Paloma Aparecida [UNESP]; Fransozo, Vivian; de Andrade, Luciana Segura [UNESP]; Almeida, Ariádine Cristine; Furlan, Michele [UNESP]; Fransozo, Adilson [UNESP] (Taylor & Francis, 2014)
The crab Hepatus pudibundus is an abundant species, part of the crustacean fauna caught as by-catch in the shrimp fishery off the Brazilian coast. This study investigated its distribution and population structure relative to measured environmental factors, sex ratio and juvenile recruitment of the species in sheltered and exposed areas in each of three bays on the northern coast of the State of São Paulo, Brazil. The crabs, along with water and sediment samples, were collected monthly from January 1998 through December 1999. A total of 8674 individuals were captured, 33.2% from Ubatumirim, 31.1% from Ubatuba and 35.7% from Mar Virado. Individuals were more numerous in the exposed areas and during the summer months. Only some of the environmental factors analysed showed any significant influence on the abundance of crabs. Of the total of crabs collected, 6239 were females (490 juveniles, 5031 adult females and 718 ovigerous females) and 2435 males (343 juveniles and 2092 adults). Females were smaller than males and more abundant in all areas. Although non-normal, the distribution of H. pudibundus can be considered stable in all three bays, as juveniles (indicating continuous recruitment) and adults of both sexes were present in most months and transects sampled. © 2014 Taylor & Francis.
Keywords: By-catch; Crustacea; ecological distribution